Оптимальная нижняя оценка для значений продолжения меры возможности на булеан множества элементарных событий - Бычков, А.С.; Иванов, Е.В. (Кибернетика и системный анализ, 2011)
Введено поняття нижньої міри можливості і за його допомогою отримано критерій існування спільного продовження мір можливості на булеан множини елементарних подій, а також критерій існування моделі збіжності за можливістю для послідовності розподілів нечітких персептивних елементів. The concept of lower possibility measure is introduced and used to obtain a criterion for the existence of common extension of possibility measures to the power set of a set of elementary events. This criterion is used to derive an existence criterion for a model of convergence in probability for a sequence of distributions of fuzzy perceptive elements.